Unveiling the sources of English speaking anxiety of a vocational school student: A narrative study - Mentari, Mentari; Abid, Abid; Bay, Indri Wirahmi (Universitas Negeri Gorontalo, 2023)
The primary aim of this study is to explore the sources of English-speaking anxiety and ascertain the learners' future expectations regarding his English language proficiency. The study was conducted at a vocational school in Central Sulawesi, Indonesia, using a narrative inquiry design. A 10th-grade student from the Hospitality and Tourism Industry class was purposively invited to participate voluntarily. Data was collected through semi-structured interview and analyzed thematically. The findings revealed that sources of the student' anxiety when speaking English included a lack of English vocabulary capacity and a lack of exposure to English as oral communication. Furthermore, the findings show that the student's future expectation of learning English as a foreign language in the classroom include becoming familiar with speaking English and to be able to talk to foreign guests without being nervous. This study highlights the need for further investigations into effective strategies to facilitate students' efforts in speaking English comfortably.